Designathons in health research: a global systematic review - Chunyan Li; Ucheoma Nwaozuru; Jason J Ong; Joseph D Tucker; Tiarney Ritchwood; Elizabeth Chen; Jamie L Conklin; Abdulhammed Opeyemi Babatunde; Warittha Tieosapjaroen; Arturo M Ongkeko; Nina T Castillo Carandang (BMJ Global Health)
Introduction A designathon is a three-stage participatory activity informed by design thinking. There is a growing literature on designathons in health. This study synthesised designathons’ effectiveness and implementation-related factors to address health challenges.Methods We searched Cochrane Library, Embase, PubMed, Scopus and the ClinicalTrials.gov registry for articles containing primary data on designathons for health from their dates of inception to 29 November 2022. We retrieved additional studies from citation searching and a complementary open call. We synthesised data on designathons’ effectiveness (ie, engagement, outputs and implementation), required resources and implementation-related factors (ie, resources, facilitators, barriers, strengths and limitations). We assessed the risk of bias using a checklist adapted from Joanna Briggs Institute Critical Appraisal tools.Results In total, 4973 citations were identified, and 42 studies were included. In total, 26 studies (62%) were from high-income countries. The median number of total participants was 49, divided into a median of 8 teams. The duration of the intensive collaboration phase ranged from 3 hours to 7 days. Common evaluation criteria were feasibility, innovation and impact. Idea and prototype outputs included mobile phone applications, educational programmes and medical devices. Interventions developed from a designathon was estimated to be highly cost-effective. The most common facilitators were interdisciplinary participants and high-quality mentorship. The most common barriers were suboptimal execution of the events, difficulties in balancing interdisciplinary participants across teams and limited support for participants along the process. There were limited data on required resources and further implementation of solutions after designathons.Conclusion Given designathons’ adaptability in terms of budget, mode of delivery, type of output and involvement of diverse participants, including end users, designathons can be implemented in a wide range of contexts to address various health issues.PROSPERO registration number CRD42023389685.